2009
DOI: 10.4049/jimmunol.0803036
|View full text |Cite
|
Sign up to set email alerts
|

Notch Activation Induces the Generation of Functional NK Cells from Human Cord Blood CD34-Positive Cells Devoid of IL-15

Abstract: The development of NK cells from hematopoietic stem cells is thought to be dependent on IL-15. In this study, we demonstrate that stimulation of human cord blood CD34 ؉ cells by a Notch ligand, Delta4, along with IL-7, stem cell factor, and Fms-like tyrosine kinase 3 ligand, but no IL-15, in a stroma-free culture induced the generation of cells with characteristics of functional NK cells, including CD56 and CD161 Ag expression, IFN-␥ secretion, and cytotoxic activity against K562 and Jurkat cells. Addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…8 Furthermore, activation of Notch signaling in HSCs has also been reported to stimulate the direct production of NK cells. 42 In that context, it is worth noting that our present study confirmed that Fli-1 loss also induced a significant increase in NK cells as already observed by others in chimeric Fli-1 Ϫ/Ϫ mice. 25 An exciting possibility suggested by our study, that could simultaneously explain both the increase in MEPs and NK cells induced by Fli-1 loss, would be therefore that Fli-1, as already reported for Ikaros, 43 might be a negative regulator of Notch signaling in HSCs.…”
Section: Discussionsupporting
confidence: 92%
“…8 Furthermore, activation of Notch signaling in HSCs has also been reported to stimulate the direct production of NK cells. 42 In that context, it is worth noting that our present study confirmed that Fli-1 loss also induced a significant increase in NK cells as already observed by others in chimeric Fli-1 Ϫ/Ϫ mice. 25 An exciting possibility suggested by our study, that could simultaneously explain both the increase in MEPs and NK cells induced by Fli-1 loss, would be therefore that Fli-1, as already reported for Ikaros, 43 might be a negative regulator of Notch signaling in HSCs.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the suppressive function of Notch in IL-15-induced cNK cell differentiation from HPC-3 cells, Notch signaling augmented IL-7-induced cNK cell differentiation from HPC-1 cells, because a substantial proportion of the cNK cell population is generated from CD34 + Lin 2 CD7 + cells, which are induced from HPC-1 cells by Notch signaling. Similarly, Notch signaling was reported to induce cNK cell differentiation from human HPCs in culture (24,26,30,45) (47). It is known that Notch signaling is essential for T cell commitment in ETPs (32,48).…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have shown that Notch signaling is required for differentiation of NCR + ILC3 from NCR 2 ILC3 and for maintenance of the NCR + ILC3 population (22,23). In humans, Notch signals enhance cNK cell differentiation from HPCs in culture (24)(25)(26)(27). However, although only one report noted that ILC2 lineage cells can be induced from postnatal thymic CD34 + CD1a 2 cells by Notch signals using OP9-DL1 cells (28), the significance of Notch signaling in the commitment of human ILCs is largely unknown.…”
mentioning
confidence: 99%
“…Several reports suggest that Notch signaling can promote development of certain NK subsets as well as their function. NK cells expressing certain T lineage markers such as CD7 + and cyCD3ε + could be generated from UCB cells in the presence of OP9 stromal cells expressing Dll1 [125] or Dll4 [126]. These human-like NK cells acquired cytolytic activity and produced granzyme B [125].…”
Section: Notch and Other Hematopoietic Cell Typesmentioning
confidence: 98%